Exploring the role and mechanisms of environmental serious games in promoting pro-environmental decision-making: a focused literature review and future research agenda - Chen, Jinsong; He, Miao; Chen, Jing; Zhang, Chugong (Frontiers in Psychology, 2024)
Environmental serious games aim to heighten players' awareness and comprehension of environmental issues, thus fostering pro-environmental decision-making. Research to date has affirmed these games' effectiveness in enhancing environmental knowledge and abilities, elevating consciousness regarding environmental matters, and promoting pro-environmental behavioral intentions and actions. Nonetheless, a detailed exploration into the precise mechanisms facilitating these impacts remains scarce. Leveraging theories of motivation, cognition, affect, and behavior, this paper outlines four hypothesized mechanisms of influence and introduces an Embodied-Enactive Cognition Model as a novel perspective. It suggests that future research should expand its inquiry into the multifaceted factors that influence pro-environmental decision-making, deepen the comprehension of the intrinsic mechanisms at play, pioneer novel research methodologies, and diversify the array of categories and contextual applications of environmental serious games.